1997
DOI: 10.1042/cs0920261
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Arterial Disease Mortality and BUPA Health Screening Data in Men, in Relation to Outdoor Temperature

Abstract: 1. Laboratory studies have shown that cold exposure causes an increase in blood pressure, cholesterol and erythrocyte count. However, whether the mild cold exposures received during everyday life are sufficient to cause such changes is unclear. 2. To test this, outdoor temperatures in central London between 1986 and 1992 were related to both haematological and blood pressure data on 50-69-year-old men attending BUPA health screening examinations in London, and to mortality in South-East England. Since any asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 22 publications
2
43
0
Order By: Relevance
“…27 In summer, a reduction in cardiovascular mortality has also been observed with a reduction in the occurrence of stroke in patients with hypertension. [28][29][30][31] The cardiovascular morbidity and mortality associated with seasonal changes may be mediated through BP response to temperature changes. In a study conducted among 1222 consecutive individuals who sought medical consultation in hypertension outpatient clinics, lower ambient temperature was associated with increased aortic pulse pressure and poor subendocardial viability ratio.…”
Section: Hypertensionmentioning
confidence: 99%
“…27 In summer, a reduction in cardiovascular mortality has also been observed with a reduction in the occurrence of stroke in patients with hypertension. [28][29][30][31] The cardiovascular morbidity and mortality associated with seasonal changes may be mediated through BP response to temperature changes. In a study conducted among 1222 consecutive individuals who sought medical consultation in hypertension outpatient clinics, lower ambient temperature was associated with increased aortic pulse pressure and poor subendocardial viability ratio.…”
Section: Hypertensionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Of the four seasons, cold winter has the highest mortality and morbidity of cardiovascular diseases in a year. [15][16][17][18] Cold temperatures make hypertension more severe in hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…Arend S.M. et al found [17] similar signifi cant decreases in serum albumin values within 24 h in heart patients both treated and control ones with nitroglycerin. Pollock D.M.…”
Section: Discussionmentioning
confidence: 81%